Research and recommended solutions on construction needs of rural infrastructure and public service facilities - Li, Jie; Gao Xiuxiu; Yang, Li; Zhang, Xiaotong (Journal of agricultural resources and environment, 2023)
针对我国农村地区基础设施和公共服务设施普遍存在缺乏统筹规划、资源配置不均衡、共享性差等问题，本研究采取现场调查、座谈交流等方式对5个典型地区18个乡镇26个村350余户居民进行设施使用满意度和需求调研，并在此基础上辨析设施配建与管理的主要影响因素。调研结果显示：村民对基础设施的满意度普遍高于公共服务设施，不同年龄和家庭收入人群的满意度和需求表现出一定的差异性。村民对基础设施的需求主要集中在设施的建设形式、使用安全性，对公共服务设施的需求主要集中在设施的便利性和服务质量。基于调研数据得出，影响农村基础设施和公共服务设施配建与管理的主要因素包括经济发展水平、资源环境条件、技术支撑能力和基层治理能力。最后，研究从区域统筹、时序协调、技术优选、治理升级4个方面提出基层政府进行基础设施和公共服务设施配建与管理的对策。Common problems of infrastructure and public service facilities in rural areas in China include lack of overall planning, unbalanced resource allocation, and poor sharing. This study surveyed the satisfaction and demands of over 350 households in 18 townships and 26 villages in five typical areas. Data from on-site surveys, informal discussions, and exchanges identified the main factors affecting the construction and management of facilities. The survey results revealed that satisfaction with infrastructure is generally higher than satisfaction concerning public service facilities. Certain differences in satisfaction and needs were evident among different ag